2013
DOI: 10.1007/s00253-013-5291-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of the lipopetides produced by Bacillus amyloliquefaciens M1 against multidrug-resistant Vibrio spp. isolated from diseased marine animals

Abstract: In this work, the antibacterial activity of the lipopeptides produced by Bacillus amyloliquefaciens M1 was examined against multidrug-resistant Vibrio spp. and Shewanella aquimarina isolated from diseased marine animals. A new and cheap medium which contained 1.0 % soybean powder, 1.5 % wheat flour, pH 7.0 was developed. A crude surfactant concentration of 0.28 mg/ml was obtained after 18 h of 10-l fermentation and diameter of the clear zone on the plate seeded with Vibrio anguillarum was 34 mm. A preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 28 publications
4
59
0
1
Order By: Relevance
“…In addition to amylosin, B. amyloliquefaciens 19b produces surfactin and antifungal fengycin (2,43). Strains of B. amyloliquefaciens producing several antibacterial and antifungal linear and cyclic lipopeptides (e.g., fengycins, iturins, and surfactins) have also been isolated from, e.g., marine environments, mangrove forests, and plant rhizospheres (30,44,45). These reports together with our results suggest that the simultaneous production of several antimicrobial substances by B. amyloliquefaciens strains is widespread in nature and offers a competitive advantage to the producer microbe.…”
Section: Figsupporting
confidence: 77%
“…In addition to amylosin, B. amyloliquefaciens 19b produces surfactin and antifungal fengycin (2,43). Strains of B. amyloliquefaciens producing several antibacterial and antifungal linear and cyclic lipopeptides (e.g., fengycins, iturins, and surfactins) have also been isolated from, e.g., marine environments, mangrove forests, and plant rhizospheres (30,44,45). These reports together with our results suggest that the simultaneous production of several antimicrobial substances by B. amyloliquefaciens strains is widespread in nature and offers a competitive advantage to the producer microbe.…”
Section: Figsupporting
confidence: 77%
“…So the culture and/or isolated cells with direct antimicrobial activity should be used as the source for novel antimicrobial substance extraction (Lai and Wong 2013). Other research confirmed that members of genus Bacillus can produce more than one type of antimicrobial metabolite (Aunpad and Panbangred 2012; Bacon et al 2012;Li et al 2012;Xu et al 2014). In addition, the strain of B. pumilus B16 or B. mojavensis J7 may produce different types, or amounts, of antimicrobial agents according to the variation in the potency of antagonism to different indicator bacteria (Table 4).…”
Section: Enzymatic Activities Of B Pumilus B16 and B Mojavensis J7mentioning
confidence: 97%
“…The results indicated that two the potential probiotic strains of B16 and J7 were closely related to Bacillus spp. which is well known for having the widely antimicrobial activity (Aunpad and Na-Bangchang 2007; Aunpad and Panbangred 2012; Li et al 2012;Xu et al 2014). The identities of 16S rRNA between strains of B16 and Bacillus pumilus ATCC 7061 and strains of J7 and Bacillus mojavensis SWFU16 were 100 and 99 % respectively (Fig.…”
Section: Molecular Biological Identifications Based On 16s Rrna Gene mentioning
confidence: 99%
“…On the other hand, the methanol extract did not exhibit antimicrobial activity against E. coli. Several lipopeptide biosurfactants obtained from Bacillus amyloliquefaciens M1 [41], Bacillus mojavensis A21 [42] and Bacillus methylotrophicus [43] showed strong antibacterial activity. …”
Section: Antimicrobial Activitymentioning
confidence: 99%